Discourses of Good Motherhood and the Policing of Young Parenthood - Varadi, Amber-Lee (Women & criminal justice, 2020)
Within a neoliberal context, youth pregnancy continues to be socially recognized as an individualized mistake, influencing young mothers by shaping and constraining their actions and lifestyle choices. Utilizing a Foucauldian and poststructural feminist lens, and drawing on interviews with 11 young mothers, this research examines how, where, and why young mothers experience forms of policing. Participants conceptualized “good” motherhood through two qualities—“being there” and “taking care of herself too”—which simultaneously reproduce and resist hegemonic discourses related to normative mothering and neoliberalism. Findings also reveal how real and perceived instances of judgement resulted in young mothers’ policing and/or self-policing.